Self-regulation of mass-media: requirements and priorities (The Journal of Psychology and Sociology, 2012)
In article the problem of self-regulation of mass-media on an example of the separate European countries is considered. Set of media technologies during modern time is the most influential agent of socialization. As the theoretical basis of a problem in article the various concepts, characterizing mechanisms of influence of mass-media on a society (by Lazarsfeld P., Noelle-Neumann Е., Lasswell H. and others) are mentioned. Formation of bodies of self-regulation of mass-media is connected with closer cooperation of journalistic community with remedial community and structures of a civil society. Self-regulation of mass-media is the, nonstate organizational system providing «social responsibility» mass-media, i.e. responsibility of mass-media for the activity not before the state on the basis of the law, and before a society on the basis of ethical standards. In article examples of regulation of mass-media in Sweden, («The Swedish council of the press»), the USA («The Commission on freedom of the press») and Germany («Press Councils») are resulted.
Keywords: media technology; media self-regulation; the modern media; the social responsibility of the media.